PENGARUH PEMANFAATAN SOSIAL MEDIA, MOTIVASI DAN PENGETAHUAN TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA EKONOMI DI UNIVERSITAS MUHAMMADIYAH SIDOARJO - Alfaruk, Muhammad Hasym (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2016)
This study aimed to analyze the influence of social media utilization, motivation and knowledge of student interest in entrepreneurship at the Economic University of Muhammadiyah Sidoarjo either partially or simultaneously. Research conducted a quantitative study. The population in this study Economy class students in 2009-2010 to 650 with a total sample of 247 students. Methods of data analysis using multiple linear regression analysis technique. The results showed that the partial use of social media and motivation significant effect on student interest in entrepreneurship at the Economic University of Muhammadiyah Sidoarjo, while knowledge has no influence on the interest in entrepreneurship in students of Economics, University of Muhammadiyah Sidoarjo. Simultaneous use of social media, motivation and knowledge significantly influence student interest in entrepreneurship at the Economic University of Muhammadiyah Sidoarjo